Der russische Angriffskrieg gegen die Ukraine und das Völkerrecht - Lange, Felix (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2023)
This text addresses the Russian war of aggression against Ukraine and the general development of international law. It focuses on three questions: What consequences does the Russian breach of the prohibition of violence have for international law as a legal order? Can Putin be held to account before the International Criminal Court? And are the individual EU sanctions being imposed on Russian citizens legal?